Multifunctional hybrid cellulose nanocrystal-gold nanoplatform and use thereof in medicine
The preparation process of CNC-Au composites is simplified by burying small-sized gold nanoparticles (AuNP) in cellulose nanocrystals (CNCs) and using lipoamide (LA) as the spacer to form Au-S bonds. Complex process and material stability problems in the prior art are obtained, and a multifunctional nanoplatform with high biocompatibility and stability is realized, which is suitable for tumor treatment.
Patent Information
- Application Number
- CN202380044452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-30
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art requires complex process flow and materials when preparing hybrid CNC-Au composite materials, resulting in the impact of the biocompatibility, stability and reproducibility of the materials, and it is difficult to realize a simple, fast and reliable preparation method.
By engaging small-sized gold nanoparticles (AuNPs) in cellulose nanocrystals (CNC) matrix and using lipoamide (LA) as spacer, Au-S bonds are formed to provide anchor points to support further functionalization, One-pot method to prepare CNC*-Au-LA composite materials to simplify the process flow.
A simplified preparation process is achieved, maintaining the biological and physical properties of the CNC, improving the biocompatibility and stability of the material, ensuring the presence of anchor points to support further functionalization, suitable for the fields of medicine and nanomedicine, especially In tumor treatment.
Smart Images

Figure CN119486764A_ABST
Abstract
Description
Prior art
[0001] Cellulose nanocrystals (CNCs) are low-cost functional and smart materials that can be easily prepared from different renewable energy sources by controlled acid hydrolysis. In particular, cellulose nanocrystals (CNCs) are derivatives of natural cellulose that can be obtained by acid hydrolysis of natural cellulose, where cellulose is exposed to sulfuric acid under controlled temperature and time period.
[0002] According to a simple description, natural cellulose molecules are derived from fibrils of natural plant cells from trees, and nanocrystals of cellulose are then obtained therefrom by acid hydrolysis.
[0003] Cellulose nanocrystals (CNCs) have become one of the most attractive natural biopolymers due to their unique biocompatibility, biodegradability, and good chemical stability, to the extent that they have great potential to be considered as a "magic bullet" for medicine, especially nanomedicine.
[0004] Small spindle-like size, rigid chain structure and large surface area (250 to 500 m 2 / g) is a unique feature that allows the preparation of advanced CNC-based nanomaterials for a wide range of application areas spanning materials and life sciences.
[0005] With regard to biological systems, the large surface area and surface hydroxyl groups enable easy functionalization and bioconjugation with specific biomolecules allowing targeting to disease sites. Then, the known protein-repelling properties of carbohydrate-based polymers make CNCs suitable for use as nanocarriers for the development of therapeutic agents, resulting in prolonged circulation in the bloodstream and delayed opsonization by phagocytes.
[0006] Additionally, it should be noted that rod morphology and surface chemistry significantly influence CNC fate: CNCs exhibited a slower renal clearance rate and, interestingly, for drug delivery applications, non-targeted nanocrystals showed low uptake in several cell types. The rigid chain structure then makes CNCs an excellent platform for the fabrication of metal nanohydrids. It is noteworthy that, from a general perspective, it is known that material composition, physicochemical properties and, therefore, surface chemistry can significantly influence the interaction with immune cells in terms of nanomaterial fate and, to some extent, induction or tolerance.
[0007] Among them, CNC-gold composites (CNC-Au) are attractive examples of hybrid nanomaterials, in which the complementary and synergistic combination of the physicochemical properties of gold nanoparticles (AuNPs) and CNCs produces unique materials with catalytic and sensing properties.
[0008] So far, three main approaches have been reported for hybrid CNC-Au composites and include: (i) in situ fabrication of AuNPs in the CNC matrix, (ii) mixing preformed AuNPs with CNCs, (iii) seeded growth schemes where AuNPs grow on a step-by-step basis. Then, less common schemes such as solid milling, microimaging, inkjet printing, electrospinning, electron beam evaporation, dip coating, and layer-by-layer assembly have recently been proposed for specific applications.
[0009] In particular, the in situ fabrication of AuNPs involves the adsorption of a gold salt (i.e., tetrachloroauric acid, HAuCl4) onto a CNC matrix followed by the reduction of the salt to metallic gold using primarily sodium borohydride (NaBH4). However, in order to ensure a narrow and homogeneous distribution of AuNPs, the use of chemically modified CNCs with molecules acting as reducing agents or stabilizers is often applied. Therefore, it is necessary to pretreat cellulose nanocrystals (CNCs) by anchoring such modified molecules to the OH groups of the glucose residues of CNCs. Thus, this pretreatment step produces significant structural changes and surface chemistry of the initial CNC composition, such as CNC quaternization, pegylation, acetylation, derivatization with polyamidoamine (PAMAM) dendrimers that impart positive charges on the CNC surface or with poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) chains or poly(diallyldimethylammoniumchloride) (PDDA), or free radical polymerization on the CNC surface. The above modifications of the CNC surface have the disadvantage of significantly changing their physical characteristics and properties, thus affecting the achievable CNC functionality and nanobio interactions.
[0010] Chinese patent CN111803629A discloses an organic-inorganic hybrid multifunctional biomaterial based on nanocellulose crystals, characterized in that it is mainly composed of nanocellulose crystals (CNC) derived from a polydopamine (PDA) coating. The CNC is completely covered with polydopamine, thereby hiding the cellulose adhesion and thus preventing interaction with cells that can only observe polydopamine. According to the Chinese patent, cellulose nanocrystals (CNC) are used as a template, and a layer of polydopamine forming a film is wrapped on the surface of the CNC. The CN111803629A Figure 1A CNC is shown covered by a dark layer, which is represented by polydopamine. In addition, it is known in the art that although polydopamine is biocompatible, it is also characterized by its own defined properties, which are very different from those of cellulose. Polydopamine is a sticky polymer that absorbs light. It is very different from cellulose and has its own functionality, which masks the cellulose.
[0011] In the Chinese patent, the cellulose covered by polydopamine is also added with long-chain polyethylene glycol (PEG-5000Da). In other words, the cellulose in the Chinese patent has no interaction with cells at all.
[0012] The biocompatibility of any cell with cellulose is changed because the relationship becomes with polydopamine or with any other modifier that covers the cellulose adhesion, rather than with the cellulose itself. The original characteristics of cellulose are obscured and lost in some way due to the presence of the change. The Chinese patent discloses how the OH groups of polydopamine can coordinate gold nanostars (AuNS). CN111803629A relates to the use of cellulose nanocrystals as a base material and polydopamine as a coupling material, which is used as a bridge between nanocellulose crystals and nano gold stars. In order to achieve this result, the Chinese patent discloses a multi-step process, resulting in changes in biocompatibility and a significant level of complexity in the manufacturing process.
[0013] All these changes significantly affect the composition and properties of the original CNCs, and also the possibility of further functionalizing the OH groups of the glucose residues of the CNCs with specific biomolecules that allow targeting of disease sites. The resulting CNC-Au composite does not contain additional anchoring points for further functionalization of the PEGylated CNC-Au composite. The lack of the possibility of further functionalization of the PEGylated CNC-Au composite is considered a significant side effect of the composite.
[0014] Some examples of modified cellulose used to prepare hybrid CNC-Au composites can be represented by cellulose ethers, cellulose lipoate, thio-labeled cellulose, quaternary ammonium, cellulose triacetate, and cellulose-polydopamine. Cellulose-dopamine is actually the substance disclosed in the above-mentioned CN111803629A. It is worth noting that the preparation of CNC-Au composites usually requires a multi-step scheme including high reaction temperature (i.e., hydrothermal reaction at 120°C for 10 hours) or the use of ionic liquids, and these are considered to be undesirable effects.
[0015] Some of the above modifications of the CNC surface are also incompatible with the next synthesis step required to stabilize the CNC suspension, thus also affecting the stability and reproducibility of the CNC-Au composites, leading to the need to have controlled reaction conditions in place (i.e. for cellulose lipoic acid). This is another side effect of the complex methods and materials.
[0016] Therefore, it is known in the art that modified cellulose loses the original biological and physical characteristics, affecting the biocompatibility, stability, reproducibility and many other characteristics of the cellulosic material (such as CNC and CNC-based compounds), while the natural characteristics of the cellulosic material are instead considered to be a part to be retained in order to obtain good results in the following uses.
[0017] On the other hand, small-sized and stable AuNPs can be prepared by using an established Brust-Schiffrin-like method, which involves reducing tetrachloroauric acid (HAuCl4) with sodium borohydride (NaBH4) in the presence of a thiol-ending ligand that ensures the formation of Au-S bonds. In some cases, lipoic acid is used to stabilize gold particles, but its use is currently known only in situations that prevent subsequent functionalization of cellulosic materials. There are articles reporting on the sulfation of α-cellulose lipoic acid and the ability of the sulfated groups to stabilize the resulting colloidal suspension of CNC-Au composites, but the reaction conditions of the sulfation protocol are incompatible with the functionality contained in the cellulose lipoic acid. In fact, lipoic acid itself is oxidized in an undesirable mode.
[0018] It is well known in the art that the complexity of materials and methods for obtaining them is undesirable and detrimental to achieving the goal of having ready-to-use materials capable of maximizing effects, especially in medical and nanomedical methods where there is a significant need to obtain results in a simple, rapid and reliable manner. In addition, the complexity of the methods / materials may confer batch-to-batch reproducibility to the manufacturing process and thus transferability of the results in clinical applications.
[0019] If tumor therapy (especially solid tumor therapy) is considered a target, it is obvious that the possibility of transferring the results in clinical application is very important; it is known in the art that reproducibility and high definition are required to make products ready for the market.
[0020] In this regard, radiotherapy is one of the most commonly used techniques for treating solid tumors. Radiotherapy uses high-energy radiation to induce cell damage, slowing down tumor growth by destroying the genetic material of the tumor. However, tumor radioresistance (mainly due to tumor-related hypoxia) and not damaging surrounding healthy tissues remain challenges. In the past, many efforts have focused on the improvement of the therapeutic ratio of radiotherapy in targeted radiation delivery and specific tumor sensitization. It is believed that radiosensitizers are panaceas because they increase the radiation dose deposition at the tumor site, thereby allowing the use of lower and safer radiation doses to non-target tissues, and obtaining the same effect on the tumor. In particular, gold nanoparticles (AuNPs) are excellent radiation absorbers due to their higher energy absorption coefficients compared to soft tissues. When interacting with radiation, they mainly enhance the generation of electron release and reactive oxygen species. The enhancement of the radiotoxicity of tumor cells internalized AuNPs has been demonstrated in vitro and in vivo.
[0021] In the past few years, several approaches for targeted delivery of AuNPs at tumor sites have been pursued to improve NP biodistribution, ensuring an increased therapeutic window.
[0022] The size, shape and surface coating of gold nanoparticles (AuNP) strongly affect cellular uptake, biodistribution and blood circulation shelf life. For this reason, small-sized (preferably ≤5nm) AuNPs are promising radiation dose enhancers, although the low driving force of their uptake and their rapid renal clearance limit the conversion to clinical. Larger AuNPs (20 to 60nm) show maximum cellular uptake, and they accumulate in the reticuloendothelial system, causing undesirable side effects. Intrinsic limitations are also relevant to the colloidal stability and biodistribution of AuNPs, which are strongly affected by the interaction of medium conditions (i.e. pH, ionic strength) and NP surfaces with biomolecules, which induce NP aggregation and encapsulation (i.e. forming protein corona shells on NP surfaces). Therefore, it is necessary to find improved materials without reducing disadvantages simultaneously.
[0023] The present inventors were able to unexpectedly discover a simple, affordable, stable, modular and improved multifunctional hybrid CNC-Au based nanoplatform.
[0024] The present inventors have also unexpectedly discovered a scalable and simple one-step method to obtain such improved multifunctional hybrid CNC-Au based nanoplatforms in a unique manner.
[0025] It should be noted that the term "cellulose nanocrystals (CNC)" according to the present invention refers to raw natural cellulose nanocrystals as starting material, preferably as CelluForce NCC TM(hereinafter also referred to as CNC**) is available on the market, while the term cellulose nanocrystals after controlled sulfation as disclosed below refers to cellulose nanocrystals obtained from CelluForce NCC in the present invention. TM (hereinafter also referred to as CNC*) are prepared starting from cellulose nanocrystals.
[0026] definition:
[0027] CNC Cellulose nanocrystals obtained from different renewable and waste sources
[0028] CNC*Sulfated cellulose nanocrystals, which are commercially available from CelluForce NCC TM (hereinafter also referred to as CNC**) starts preparation.
[0029] CNC** Commercially available CelluForce NCC TM .
[0030] CNC-Au hybrid nanomaterials, which consist of gold nanoparticles embedded in a cellulose nanocrystal matrix (both CNC* and CNC**).
[0031] NP nanoparticles
[0032] AuNP gold nanoparticles
[0033] LA Lipoic Acid
[0034] CNC-Au-LA hybrid nanomaterials, which consist of gold nanoparticles embedded in a cellulose nanocrystal matrix (both CNC* and CNC**) and carry a lipoamide spacer attached on the gold surface via the formation of Au-S bonds and are provided with a terminal alkyne moiety.
[0035] CNC-Au-Tm hybrid nanomaterials, which consist of gold nanoparticles embedded in a cellulose nanocrystal matrix (both CNC* and CNC**) and carry a lipoamide spacer attached to the gold surface through the formation of Au-S bonds. The lipoamide spacer is linked to the tumor targeting moiety (Tm) through a tetrazole group.
[0036] Tm tumor targeting moiety. In some embodiments of the invention, Tm is a glucose (Glc) or mannose (Man) or lactose (Lac) residue with a PEG spacer at the anomeric position (in the case of lactose at the terminal monosaccharide (Glc) residue). Tm is linked to the lipoamide spacer on the surface of CNC-Au-LA via a tetrazole group.
[0037] HEPES 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid, which is a buffer used in cell culture to better stabilize and maintain physiological pH conditions.
[0038] Dulbecco's Modified Eagle Medium (DMEM) is a commonly used basal culture medium for culturing many mammalian cells in vitro.
[0039] DEF dose enhancement factor
[0040] SER sensitivity enhancement ratio
[0041] BODIPY-like fluorescent probes are derivatives of 4,4'-difluoro-4-borane-3a,4a-diaza-s-indacene.
[0042] CNC*-Au-BODIPY hybrid nanomaterials, which consist of gold nanoparticles embedded in a cellulose nanocrystal matrix prepared from CNC** and carry a lipoamide spacer attached on the gold surface through the formation of Au-S bonds. The lipoamide spacer is linked to a BODIPY-like fluorescent probe via a tetrazole group.
[0043] CNC*-Au-Glc-BODIPY bifunctional hybrid nanomaterials, which consist of gold nanoparticles embedded in a cellulose nanocrystal matrix prepared from CNC** and carry a lipoamide spacer attached on the gold surface through the formation of Au-S bonds. The lipoamide spacer is linked to a glucose residue (Glc) and a BODIPY-like fluorescent probe through a tetrazole group. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagram of the CNC*-Au-LA composite material described in the present invention is shown along with the versatility of the proposed nanomaterial in terms of multiple functionalization sites of both the OH groups of CNCs and the alkyne residues on the surface of AuNPs with bioactive head groups and functional stabilizers.
[0045] Figure 2 The synthetic strategy for preparing CNC*-Au-LA described in the present invention is shown.
[0046] Figure 3Transmission electron microscopy of CNC*-Au-LA is shown. The size of AuNPs was evaluated according to Schneider, CA, Rasband, WS, Eliceiri, KW "NIH Image to ImageJ: 25 years of image analysis". Nature Methods 9, 671-675, 2012. AuNPs 5±1 nm.
[0047] Figure 4 The chemistry that can be used to conjugate bioactive head groups and functional stabilizers on CNC*-Au-LA is shown.
[0048] Figure 5 Shown is a synthetic strategy for preparing monofunctional and bifunctional CNC*-Au conjugates with bioactive head groups via iterative step-by-step conjugation reactions described in this invention.
[0049] Figure 6Schematic diagram of CNC*-Au conjugates described in the present invention is shown. In particular, composite materials with Tm, wherein Tm=glucose (i.e., CNC*-Au-Glc) or Tm=mannose (i.e., CNC*-Au-Man) or Tm=lactose (i.e., CNC*-Au-Lac); biologically active head group=BODIPY (as a representative example of a fluorescent probe, i.e., CNC*-Au-BODIPY) or biologically active head group=2-aminoethanesulfonic acid (named taurine) (as a representative example of the possibility of further functionalizing CNC*-Au-LA on the OH group of CNC*, i.e., CNC*-Au-taurine); bifunctional conjugates with two biologically active head groups (i.e., CNC*-Au-Glc-BODIPY and CNC*-Au-LA-taurine-BODIPY). Reaction conditions: a. CuSO4: sodium ascorbate, H2O, azido-PEG-Tm (where Tm = Man or Glc) (2.0 equivalents); b. CuSO4: sodium ascorbate, H2O, azido-PEG-Glc (0.3 equivalents); c. CuSO4: sodium ascorbate, DMF, BODIPY (0.5 equivalents); d. CuSO4: sodium ascorbate, H2O, azido-PEG-Lac (1. 5 equivalents); e.CuSO4: sodium ascorbate, H2O, azido-PEG-Lac (0.5 equivalents); f.CuSO4: sodium ascorbate, H2O, azido-PEG-Lac (0.15 equivalents); g.CuSO4: sodium ascorbate, DMF, BODIPY (0.1 equivalents); h.DMSO, carbonyldiimidazole (CDI), Na2CO3.
[0050] Figure 7 CNC*-Au (left) and CNC**-Au (right) resuspended as described in Materials and Methods, at a concentration of 1.0 mg / ml in water, images were acquired on an EVOS fl microscope (Thermofisher) without filters. Magnification was up to 40× in the left image, and no major signs of aggregation were observed (white bar represents 100 μm), and 10× in the right image (white bar represents 400 μm).
[0051] Figure 8 Schematic diagram of CNC**-Au conjugates described in the present invention is shown. In particular, composite materials with Tm, wherein Tm = glucose (i.e. CNC**-Au-Glc) or Tm = mannose (i.e. CNC**-Au-Man) or Tm = fucose (i.e. CNC**-Au-Fuc). Reaction conditions: a. CuSO4: sodium ascorbate, H2O, azido-PEG-Tm (where Tm = Man, or Glc, or Fuc) (2.0 equivalents).
[0052] Fig. 9 CNC**-Au-Glc (left) and CNC**-Au-Man (right) were resuspended as described in Materials and Methods, and 24 hours later, the concentration was 10ug / ml in complete cell growth medium (DMEM+NA (North American fetal bovine serum)), and the images were acquired on an EVOS fl microscope (Thermofisher) without a filter. At 4x magnification, major signs of aggregation were observed (white bars represent 1000μm).
[0053] Fig.10 An image of an atomic force microscopy (AFM) image of sulfated CNC* is shown.
[0054] Fig.11 AuNP uptake by human triple negative breast cancer cells (MDA-MB-231 cell line) and healthy breast cells (MCF-10A cell line) is shown. Cells were treated with CNC*-Au-LA, CNC*-Au-Glc and CNC*-Au-Man.
[0055] Fig.12 Shown are the log10 survival fractions of MDA-MB231 (upper panel) and MCF10a (lower panel) colonies after x-ray combined treatment with CNC*-Au functionalized with mannose (left panel) or glucose (right panel) at the concentrations reported in the legend. Data are from 2 independent experiments, and each experiment was repeated 2 times (n=4).
[0056] Fig.13 Turbidimetric assay of 0.05% CNC*-Au-Man with 10 μM ConA, 1 mM MnCl2 in 10 mM HEPES (pH 7.4); B. Turbidimetric assay of 0.05% CNC*-Au-Man with different concentrations of ConA, 1 mM MnCl2 in 10 mM HEPES (pH 7.4) after 60 minutes.
[0057] Fig.14 Normalized luminescence of MDA-MB231 (left) and MCF10a (right) cells treated for 24 hours with increasing concentrations of CNC*-Au-Glc and CNC*-Au-Man (0, 2.5, 5, 10, 20, 50 and 100 μg / ml) without X-ray treatment, measured by cell titer glo as described in Materials and Methods. Each concentration was repeated 3 times (n=3).
[0058] Table 1 Fig.17) shows four tables divided by cell type (MDA-MB231 upper table and MCF10a lower table) and by CNC*-Au-LA functionalized with mannose (left table) or glucose (right table). Columns indicate the concentration of CNC*-Au conjugate treatment, DEF, SER and uptake values μg / L and relative standard deviation calculated based on 3 replicates.
[0059] Fig.15 Shown are the log10 survival fractions of A375 melanoma cell colonies after x-ray treatment in combination with CNC*-Au-Man and CNC*-Au-Glc functionalized with mannose (left panel) or glucose (right panel) at the concentrations reported in the figure legend. Data are from 2 independent experiments, and each experiment was repeated 2 times (n=4).
[0060] Fig.16 Normalized luminescence of A375 melanoma cells treated for 24 hours with increasing concentrations of CNC*-Au-Glc and CNC*-Au-Man (0, 2.5, 5, 10, 20, 50 and 100 μg / ml) without X-ray treatment, measured by cell titer glo as described in Materials and Methods. Each concentration was repeated 3 times (n=3).
[0061] Table 2 Fig.18 ) shows two tables of A375 melanoma cells divided by CNC*-Au-LA functionalized with mannose (left table) or glucose (right table). The columns indicate the concentration of CNC*-Au-Glc and CNC*-Au-Man treatments, DEF, SER and uptake values μg / L and relative standard deviation calculated from 3 replicates.
[0062] Fig.19 Shown are flow cytometric analysis of U251 glioblastoma cell viability 24 hours after combined treatment with x-rays and 20 μg / mL of CNC*-Au-Glc as determined by propidium iodide exclusion (Panel A), and the log10 surviving fraction of U251 glioblastoma cells after combined treatment with x-rays and 10 μg / mL of CNC*-Au-Glc as determined by colony formation (Panel B). Summary of the invention
[0063] The present invention relates to simple, affordable, stable, modular and improved multifunctional CNC*-Au based nanoplatforms, related conjugates and / or compositions containing the same ( Figure 1 ).
[0064] The present invention also relates to the use of such multifunctional CNC*-Au-based nanoplatforms, related conjugates and / or compositions containing them in medicine (preferably nanomedicine). More preferably, the present invention relates to the use of such multifunctional CNC*-Au-based nanoplatforms, related conjugates and / or compositions containing them in the treatment of tumors, preferably solid tumors, and more preferably the solid tumors are selected from breast cancer, uterine cancer, brain and central nervous system cancer, lung cancer, liver cancer, kidney cancer, testicular cancer, pancreatic cancer, skin cancer, thyroid cancer, intestinal cancer, head and neck cancer, ovarian cancer, gastric cancer, colon cancer, bladder cancer, prostate cancer and urinary tract cancer, eye cancer, oral cancer and oropharyngeal cancer, HIV / AIDS-related cancers, hematopoietic cancer and lymphoma, and sarcomas of various tissues.
[0065] Still more preferably, breast cancer is represented by triple negative breast cancer, brain and central nervous system cancer is represented by glioblastoma and skin cancer is represented by melanoma.
[0066] In addition, the present invention also relates to the use of such multifunctional CNC*-Au-based nanoplatforms, related conjugates and / or compositions containing the same in radiotherapy, immunotherapy, photodynamic therapy, boron neutron capture therapy (BNCT) and cancer diagnosis.
[0067] The present invention also relates to a scalable, simple, one-step method to obtain multifunctional CNC*-Au-based nanoplatforms with improved properties. Figure 2 ).
[0068] According to the present invention, small gold nanoparticles (AuNPs) with spacers having terminal chemical reporters are stably embedded in a cellulose nanocrystal (CNC*) matrix ( Figures 1 to 2 The size of the gold nanoparticles according to the present invention is preferably ≤5 nm ( Figure 3 ).
[0069] According to the present invention, the spacer is preferably a bifunctional monodentate or bidentate molecule with a thioalkyl group, such as mercaptoacetic acid (MAA), mercaptosuccinic acid (MSA), mercaptopropionic acid (MPA) as a monodentate molecule, and α-lipoic acid (DHLA) or its derivatives, i.e., α-lipoic acid conjugated to the primary amino group of an alkyne amine (i.e., lipoamide (LA) in the present invention) or the primary amino group of an ethylenediamine-N,N-acetoacetic acid residue (EDADA) as a bidentate molecule.
[0070] Lipoic acid amide (LA) according to the present invention is a monocarboxylic acid amide (LA) produced by the formal condensation of the carboxyl group of α-lipoic acid with propargylamine. Figures 1 to 2 ). The terminal chemical reporter according to the invention is an alkyne residue, such as propyne, butyne, cyclooctine and its derivatives, such as
[0071] OCT,MOFO,DIFO,DIMAC,COMBO,DIBO,DIBAC,BARAC,BCN,TMTH.
[0072] It produced a hybrid smart nanoplatform of cellulose nanocrystals and gold nanoparticles, named CNC*-Au-LA( Figures 1 to 2 The hybrid cellulose nanocrystal-gold nanoparticles of the present invention are interpreted as providing at least one and at most two easily accessible and orthogonal anchoring points on their surface, which are preferably represented by the OH groups of the glucose residues of the CNC and the alkynes on the Au surface ( Figure 5 The term "hybrid" refers to gold nanoparticles (AuNPs) and CNCs together. Thus, the present invention provides CNC-Au composites in which the surface modification does not significantly affect the composition and properties of the original CNCs, but ensures the presence of anchoring points for further multifunctionalization of the CNC surface ( Figure 4 ).
[0073] In fact, according to the invention, these anchoring points can be used to covalently conjugate at least one and preferably up to three structurally different functional groups. According to a preferred embodiment of the invention, the at least one and up to three functional groups consist of at least one biologically active head group together with an additional functional stabilizer ( Figure 6 The CNC*-Au conjugate in which the functional stabilizer is a sulfate group) is represented.
[0074] According to the present invention, a hybrid smart nanoplatform of cellulose nanocrystal gold nanoparticles (CNC*-Au-LA) with at least one and up to three functionalities is considered as a cellulose nanocrystal gold nanoparticle material containing a targeting molecule (CNC*-Au-Tm, Figure 6 ). The targeting molecule (Tm) is discussed below based on the bioactive head group. Then, the BODIPY fluorescent probe ( Figure 6 ) as a model example of the possibility of conjugating up to two bioactive head groups on a gold surface. Then, 2-aminoethanesulfonic acid (taurine) was selected as a model example of the possibility of conjugating bioactive head groups on a CNC surface, despite the presence of a functional stabilizer ( Figure 6 ).
[0075] According to the present invention, the biologically active head group (such as a targeting group) and the gold nanoparticles (AuNP) define the biological characteristics of the hybrid nanomaterial, which provides a cellulose nanocrystal conjugate that is able to specialize in (expert) specific, specialized biological properties and also has the ability to reach the desired site of action; due to their characteristics, these conjugates can be used to treat different diseases, provide improved efficacy and reduce off-target side effects, and in particular provide the effect of delivering the nanomaterial to a specific desired site of action (preferably to a tumor site for specific tumor treatment).
[0076] According to the present invention, the biologically active head group may comprise structurally different biologically active molecules, which define the biological activity of the material and can be selected from the following disease-related: i) antigens, such as tumors, pathogens including bacteria and viruses, and / or autoimmune diseases; ii) immune cell targeting molecules, such as sugars (including monosaccharides, disaccharides, trisaccharides, tetrasaccharides and oligosaccharides), nucleotides, lipids, peptides; iii) targeting receptors, such as carbohydrate binding receptors (i.e. DC-SIGN, Langherin, Mincle, mannose receptor); peptide binding receptors; nucleotide binding receptors (i.e. Toll-like receptors) and / or lipid binding receptors (i.e. CD1d, Toll-like receptors); iv) molecules targeting tumor-associated receptors, such as glucose transporters (GLUT), mannose receptors, folate receptors, CD44, galectins, ASGP receptors (see the examples of CNC*-Au-Man, CNC*-Au-Glc, CNC*-Au-Lac, Figure 6 ); v) fluorescent probe (see example CNC*-Au-BODIPY, Figure 6 ); vi) radionuclide probes for PET and / or SPECT; and vii) boron cage molecules.
[0077] According to the present invention, the preferred biologically active head group is a carbohydrate, more preferably a sugar, and even more preferably selected from glucose and mannose, lactose, fucose, rhamnose, Lewis-type antigen (i.e., Lewis a , Sialyl Lewis a Lewis X , Sialyl Lewis X Lewis b , Sialyl Lewis b ), glucuronic acid, carbohydrate mimics. According to a preferred embodiment, the functionalization is three functionalizations and covers glucose (glucose, Glu), mannose (mannose, Man) and lactose (lactose, Lac).
[0078] According to the present invention, the design and preparation of CNC*-Au-LA has been defined taking into account parameters that ensure a bench-to-bedside perspective, meaning the transition from basic research to the application of the research itself. In particular: a) colloidal stability of nanoparticle dispersions in different media; b) manufacturing methods in terms of (i) cost, (ii) green and scalable protocols with high batch-to-batch reproducibility ( Figure 2 ); c) loading of functional molecules on the NP surface (see examples of CNC*-Au-Lac, CNC*-Glc-BODIPY, Figure 6 ) is a key bottleneck that often significantly affects the bench-to-bedside translation of NPs.
[0079] In addition, the increased complexity of multifunctional nanoparticles (NPs) needs to be carefully considered when attempting to graft multiple cargoes onto their surfaces. In fact, time- and cost-consuming stepwise protocols involving multiple conjugation reactions and purification processes often result in low yields, difficulty in scale-up, and potential heterogeneity in formulations.
[0080] According to the present invention, it was also unexpectedly found that a method for the manufacture of hybrid nanomaterials is obtained that can comply with all functionalizations that allow the presence of biologically active head groups (see Figure 1 and Figures 5 to 6 ).
[0081] First, the manufacturing method of the present invention provides an in situ preparation of gold nanoparticles (AuNPs) (e.g. Figure 2 ). The single step, called one-pot, was quite unexpected and represents a major advantage in avoiding excessive complexity.
[0082] The manufacturing method according to the present invention comprises: i) using cellulose nanocrystals (CNC) as starting material; the starting material is very important to ensure the final improved nanoplatform (CNC* vs CNC**, Figure 7 ); ii) using a spacer (i.e., LA) as a gold stabilizer and reducing the gold salt to tetrachloroauric acid (HAuCl4) using sodium borohydride (NaBH4). According to a preferred embodiment, the spacer of the present invention may be a monodentate spacer or a bidentate spacer, wherein monodentate means the presence of a single sulfide group that forms an Au-S bond with a terminal group (e.g., carboxyl, amine, and azide), and bidentate means the presence of two sulfide groups (e.g., lipoic acid or DHLA-EDADA); more preferably, the spacer of the present invention is α-lipoamide (LA).
[0083] The spacer is installed in situ on the gold surface in a one-pot process with the help of a solvent, preferably a solution containing methanol / water in a ratio of 20:1 to 10:1, preferably a ratio of about 10:1 ( Figure 2 The solvent is crucial for the in situ installation of the spacer on the gold (Au) surface in the one-pot process according to the present invention; this ensures the dispersion of all reaction components ( Figure 2 ). The spacer according to the present invention is alpha-lipoic acid amide (LA) and the ratio of the methanol:water mixture is 10:1.
[0084] In more detail, the method of the present invention comprises:
[0085] a) Preparation of CNC*: Raw cellulose nanocrystals are treated with a sulfating agent (preferably a mixture of SO3 / pyridine) and a solvent (preferably dimethyl sulfoxide (DMSO)) to obtain cellulose nanocrystals with controlled sulfation ( Figure 2 );
[0086] b) Preparation of CNC*-Au-LA: The CNC* with controlled sulfation as obtained in step a) was treated with HAuCl4 / NaBH4, lipoamide (LA) in methanol / water solution to obtain hybrid nanoplatforms of CNC*-Au-LA.
[0087] According to the present invention, the preparation of CNC*-Au-LA as described in step b) above is carried out as a one-pot reaction.
[0088] Then, the CNC-Au-LA obtained according to the method of the present invention is easily purified by dialysis as the final passage.
[0089] According to this method, the size is preferably ≤ 5 nm, more preferably about 5.0 ± 1.0 nm ( Figure 3 ) are stably embedded on a cellulose nanocrystal (CNC) matrix, avoiding the need for an additional derivatization step on the CNC and ensuring a one-pot procedure. The possibility to avoid an additional derivatization is a great improvement, simplifying the method and maximizing the efficiency of the obtained nanoplatform.
[0090] Indeed, any additional derivatization step, which is usually necessary to obtain a uniform nanoparticle distribution, is considered by those skilled in the art to be an undesirable complication, believed to affect the composition and properties of the final nanoplatform.
[0091] For example, the above-mentioned Chinese patent CN111803629A discloses the use of polydopamine (PDA) for the additional derivatization of cellulose materials, which has the OH groups of polydopamine acting as coordinating gold particles, resulting in a favorable increase in AuNPs. As described above, this produces a polydopamine layer with a significant complexity spectrum wrapped on the CNC surface. No other functionalization possibilities are disclosed in CN111803629A.
[0092] According to the present invention, the surface of gold nanoparticles (AuNPs) is provided with terminal reactive groups for customizing the surface of cellulose nanocrystal-gold-α-lipoamide material (CNC*-Au-LA surface, Figure 2 and Figures 5 to 6 ), which ensures the multifunctionality of the nanoplatform and the fine tuning of its biological activity.
[0093] For cellulose nanocrystals (CNCs), different acids can be used for their preparation, and their selection can affect the dispersibility and colloidal stability of cellulose nanomaterials (CNCs). The colloidal stability of nanoparticles (NPs) is affected, and in particular, cellulose nanomaterials derived from sulfuric acid hydrolysis are easily dispersed in water. In the initial attempt to prepare CNC-Au-LA, the inventors directly used raw CNC** (CelluForce NCC TM ). It is a sulfated cellulose nanomaterial in which there is approximately one sulfate group for every six glucose residues. The potential was -39 mV ± 2 and the hydrodynamic diameter was 70 nm. However, it was noted at this time that the reaction conditions used to obtain CNC-Au-LA affected the dispersibility of the resulting hybrid CNC**-Au-LA nanomaterial, due to the reduction of some sulfate groups under these conditions; this effect corresponds to the disadvantages described in the literature regarding similar CNC substrates, and it prompted the inventors to improve the structure of CNC** to improve the dispersibility. This led to the formation of aggregates of the CNC**-Au-LA aqueous dispersion, which was confirmed by dynamic light scattering analysis (hydrodynamic diameter of CNC**-Au-LA = 2935 ± 462 nm vs original CNC** = 70 nm), resulting in low reproducibility in further functionalization steps and significantly limiting the biological applications of the NPs. Then, any attempt to improve the dispersibility of CNC**-Au-LA and its stability in water failed, and significant aggregation of the material occurred ( Figure 7 However, the functionalization of CNC**-Au-LA is carried out according to the present invention via an azide-alkyne cycloaddition reaction ( Figure 8), finally in the presence of a catalyst which may be represented by copper. Preferably, in the case where copper is used as a catalyst for the reaction, it is in the form of CuSO4. In particular, Tm (e.g. glucose (Glc), mannose (Man) and fucose (Fuc) glycosides) carrying a PEG spacer at the anomeric position are used for conjugation. However, significant aggregation of CNC**-Au conjugates was observed in complete cell growth medium ( Fig. 9 ). Therefore, such composition of CNC**-Au composites does not allow further evaluation of the biological activity of the conjugates with cells.
[0094] Therefore, the composition of CNC used as starting material needs to be carefully designed to overcome this problem. In order to maintain the structure and composition of CNC and avoid modifications that may affect the general unique properties of this nanomaterial, the inventors unexpectedly found that by adjusting the degree of sulfation of the original CNC**, it is possible to use the same functional groups already contained in the original CNC** with minimal modification.
[0095] The degree of sulfation (DS) imparts water dispersibility and, therefore, colloidal stability to CNC dispersions in water. However, high DS produces NP surfaces with a higher negative charge (lower Potential values), which may also affect biological properties (e.g., toxicity and cellular uptake), as well as macromolecular conformation, which can directly affect physicochemical characteristics. Therefore, fine tuning of the degree of CNC sulfation is another challenging step. The inventors were unexpectedly able to control the sulfation of cellulose nanocrystals, obtain uniformity of the reaction mixture, and avoid any safety issues due to the use of complex reagents (e.g., chlorosulfonic acid).
[0096] In addition, the inventors were able to control the standard deviation (DS) of the sulfation degree of cellulose nanoparticles and the undesirable and severe depolymerization of cellulose nanoparticles. CNC* was analyzed by atomic force microscopy (AFM) ( Fig.10 ), and it shows that the CNC* maintains the same shape as the original CNC** under these conditions.
[0097] All parameters related to the type of raw cellulose nanocrystals (CNC) used as starting material for the present invention are relevant to obtaining the desired nanoplatform; in particular, the preferred molecular weight is between 14700 Da and 27850 Da, and the initial source is preferably raw cellulose (CelluForce NCC TM ).
[0098] According to a preferred embodiment of the present invention, the cellulose nanocrystals (such as Figure 2The sulfation degree (DS) of CNC* reported in the literature is 0.114 ± 0.007 (original cellulose - CelluForce NCC TM (DS of CNC**) = 0.028). The sulfation of the present invention is scalable, and it provides cellulose nanocrystals (CNC*) with controlled sulfation, which carry additional sulfate groups as functional stabilizers, with high batch-to-batch reproducibility. The sulfation step according to the present invention is carried out on the cellulose nanocrystals using a commercially available and safe sulfation reagent, which is preferably represented by SO3-pyridine or SO3-NEt3, more preferably represented by SO3-pyridine. According to the present invention, the ratio of such a sulfation reagent to the glucose units of the cellulose nanocrystals is preferably 12:1 to 1:1, more preferably about 1.5:1.
[0099] The sulfation provides controlled sulfation of CNC, and the reaction preferably occurs in the presence of a solvent, more preferably the solvent is dimethyl sulfoxide (DMSO) or N,N-dimethylacetamide (DMA). Even more preferably, the solvent is dimethyl sulfoxide (DMSO).
[0100] The choice of solvent is also crucial for the present invention. It is known that raw cellulose nanocrystals are sensitive to reaction temperature, wherein known techniques are generally based on warm DMA (120°C for 1 hour) in the presence of LiCl. In contrast, the present invention unexpectedly found good dispersibility of raw cellulose nanocrystals (CNC**) in DMSO, thus allowing mild reaction conditions, which preferably last for 4 hours at about 25°C (see Experimental). This is a valuable result. Due to the possibility of carrying out the method under mild reaction conditions, the present invention avoids any depolymerization side reactions, which usually occur in commonly used sulfation schemes including high reaction temperature steps (such as, for example, in terms of temperatures of 60°C to 110°C).
[0101] The addition of three batches of SO3-pyridine reagent proved to be essential for the reproducibility of the protocol and the homogeneity of the reaction mixture. The inventors unexpectedly found that the reaction was more successful if carried out in a controlled manner, adding the SO3-pyridine reagent in a graded schedule (i.e. three batches, one per hour, see experiments), thereby avoiding gelation of the reaction mixture. It is worth noting that such controlled sulfation of the CNCs according to the invention does not affect the possibility of treating the OH groups of the glucose of the cellulose to further functionalize the nanoplatform ( Figure 2 ,as well as Figure 6 The sulfation according to the invention does not react all primary OH groups of cellulose, but some OH groups remain open for further functionalization (see e.g. Figure 6The model sample in CNC*-Au-taurine).
[0102] An advantage of the manufacturing method according to the present invention is that the hydrodynamic diameter and surface charge of the cellulose nanoparticles do not change during the sulfation process of the starting material. In more detail, the diameter of the cellulose nanoparticles (original CNC**) as the starting material is about 70 nm, and the diameter of the cellulose nanoparticles (CNC*) that become cellulose nanoparticles with controlled sulfation after the sulfation step is about 57 nm (CNC*=57 nmvs original CNC**=70 nm). The surface charge of the cellulose nanoparticles (original CNC**) as the starting material is -39±2 mV, and the surface charge of the cellulose nanoparticles with controlled sulfation is -45±2 mV (CNC*=57 nmvs original CNC**=70 nm). Potential = -45 ± 2 mV vs. original CNC** -39 ± 2 mV). These values are considered comparable and no modification is required. According to the present invention, CNC*-Au-LA ( Figure 2 ), and a significant improvement in dispersibility and colloidal stability was obtained compared to the CNC*-Au-LA composites obtained starting from pristine CNC**, where the cellulose nanocrystals were not sulfated ( Figure 7 ). Thus, sulfation of pristine CNCs ensures a scalable and modular approach for further functionalization of CNC*-Au-LA and obtaining CNC*-Au-Tm conjugates with high batch-to-batch reproducibility ( Figure 6 ), and thus the possibility of using these conjugates and related compositions containing them in biological applications, leads to the use of conjugates and related compositions in medicine. According to the present invention, functionalization is carried out by azide-alkyne cycloaddition reaction ( Figure 3 and Figures 5 to 6 ) is carried out, and finally in the presence of a catalyst which can be represented by copper. Preferably, in the case where copper is used as a catalyst for the reaction, it is in the form of CuSO4.
[0103] The functionalization according to the present invention is based on chemistry and key features which can be listed as:
[0104] Head base load control (see CNC*-Au-Lac, Figure 6 ),
[0105] ·Control of functional stabilizer loading (see CNC*, Figure 2 ),
[0106] Grafting one to three (3) different head groups (CNC*-Au-Tm (where Tm = Glc or Man or Lac), CNC*-Au-BODIPY, CNC*-Au-Glc-BODIPY) on the surface of the nanomaterial, Figure 6 ),
[0107] Grafting of one to two (2) different head groups (CNC*-Au-Glc-BODIPY, Figure 6 ),
[0108] High batch-to-batch reproducibility ( Figure 2 CNC*-Au-LA and Figure 6 CNC*-Au-Man in, see experiment),
[0109] · Control of biological properties, and
[0110] Scalable manufacturing methods ( Figure 2 ).
[0111] According to the present invention, up to two (2) different bioactive head groups can be grafted onto the alkyne residue via click chemistry, while a third bioactive head group can be conjugated to the OH group of cellulose.
[0112] Such types of results are achievable due to the unique structure and composition of the CNC*-Au-LA materials according to the present invention. The presence of controlled amounts of lipoamide (LA) units and the type of chemistry selected for conjugation represented by the azide-alkyne cycloaddition reaction ensures (i) control of head group loading by simply adjusting the equivalents of the azide-bearing reagent used (see the examples of CNC*-Au-Lac and CNC*-Au-Glc, Figure 6 ) and (ii) an iterative stepwise conjugation reaction that allows the installation of up to two different bioactive head groups on the same anchoring point (alkyne residue) on the gold surface ( Figures 5 to 6 ), with high batch-to-batch reproducibility. Depending on the solubility of the reactive head group, the conjugation reaction can be carried out in both water and polar organic solvents (e.g., DMF, DMSO).
[0113] like Figure 5 As shown in , functionalization according to the invention is performed using an azide-alkyne cycloaddition reaction (CuAAC) to produce a monofunctional CNC*-Au conjugate, which in turn can be subjected to an additional functionalization process in the same manner by another azide-alkyne cycloaddition reaction (CuAAC), adding a second functionalization to obtain a difunctional CNC*-Au conjugate. The head groups of the invention are biocompatible and readily available monosaccharide and disaccharide derivatives selected as targeting moieties. As described above, these are preferably glucose (Glc), mannose (Man) or lactose (Lac) ( Figure 6 ), which was used to demonstrate preferential delivery of cargo into selected cells by targeting receptors overexpressed on cancer cells (i.e., GLUT channels, mannose receptors).
[0114] According to one embodiment of the present invention, the inventors have proposed the design and use of new, specially engineered materials as disclosed above, as functional and tumor-specific nanoradiosensitizers, intended to enhance radiation cytotoxicity at tumor sites by targeted delivery of functionalized AuNPs stably embedded in a non-toxic and biocompatible cellulose nanocrystal (CNC) matrix. Due to the shape and size of the CNC matrix, this hybrid nanomaterial provides efficient accumulation of small AuNPs within tumor cells, thereby avoiding the rapid turnover associated with small nanoparticles. According to this embodiment, tumor targeting is achieved by utilizing small biomolecules (monosaccharides) that target specific receptors expressed on cancer cells. According to the present invention, the nanomaterials designed by the inventors are able to increase radiation dose deposition at tumor sites, thereby allowing the use of lower and safer radiation doses for non-target tissues while obtaining the same tumor effect, or improving the therapeutic effect while delivering the same dose for radiation-resistant tumors. This prevents healthy cells or tissues from being exposed and producing too many side effects. As explained, the material consists of small AuNPs functionalized with sugar head groups on their surface as tumor targeting molecules and stably embedded in non-toxic and biocompatible cellulose nanocrystals as disclosed above.
[0115] According to the present invention, CNC*-Au-Tm acts as a so-called "Trojanhorse" that allows internalization and accumulation of AuNPs in tumor cells by specifically targeting glycan-binding proteins (GBPs) (over) expressed on the surface of tumor cells. Notably, the CNC carrier ensures stable AuNP dispersion, overcomes the aggregation of AuNPs in the cell medium, and avoids rapid cellular turnover of small AuNPs. Compared with other methods, the carbohydrate nature of the carrier prevents the formation of protein coronas, which usually affect NP efficacy, thereby improving biodistribution and reducing NP clearance. In addition, according to a preferred embodiment, some of the following major challenges in this field have been addressed and solved.
[0116] 1. The amount of gold radiosensitizer used during treatment significantly affects translational research and limits its application in the clinic. In this regard, the lower gold (Au) amounts described so far are in the range of about 100 to 200 ug / mL, while the highest amount used according to the present invention is in the range of 1.0 to 2.0 ug / mL, preferably about 20 ug / mL of CNC-Au-Tm, making the preferred final gold (Au) amount about 2.0 ug / mL ( Fig.11 ).
[0117] 2. The amount of gold (Au) internalized into tumor cells and its turnover. This parameter significantly affects the possibility of improving radiation dose absorption (due to higher Z), thus affecting the radiation effect at the tumor site. According to a preferred embodiment of the present invention, small-sized gold nanoparticles (AuNPs), preferably measuring less than 5nm (<5nm), are promising radiation dose enhancers, although their low driving force for uptake and their rapid renal clearance limit their translation to the clinic. According to the present invention, the use of cellulose nanocrystals (CNCs) as a scaffold for targeted delivery of radiosensitizers into tumor cells allows for mitigation of rapid turnover and provides preferential accumulation at the tumor site.
[0118] 3. The dose enhancement factor (DEF) achieved. This parameter clearly shows the efficiency of the treatment method (see Experimental and Table 1- Fig.17 ). All the following efforts reported so far in the art prior to the present invention are known to result in approximately 3.0 to 8.0×10 4 Maximum AuNP uptake by NPs / cell: e.g. cell cycle synchronization using liposome-based nanocarriers, targeting moieties (e.g. example folic acid), or specific stress conditions (e.g. example cell starvation treatments that increase the extent of gold (Au) internalization into tumor cells).
[0119] Unexpectedly, if Fig. 9 As reported in , the results of the present invention show that the CNC*-Au-Tm composite material of the present invention is able to deliver a three-fold higher concentration of AuNPs to MDA-MB-231 cells (i.e., CNC*-Au-Man: 3.03×10 5 NP / cell; CNC*-Au-Glc: 3.33×10 5 NP / cell, Fig.11 In addition, the presence of mannose or glucose residues in CNC*-Au-Man and CNC*-Au-Glc significantly increased the cellular uptake by 73% and 87%, respectively, compared with non-functionalized CNC*-Au-LA ( Fig.11 The inventors have used two different methods to evaluate the biological effects of CNC*-Au-Tm on MDA-MD-231 cells. In the first assay, the inventors tested the short-term response of cancer cells 24 hours after irradiation. In the second assay, the ability of irradiated cells to produce colonies up to 14 days after X-ray has been evaluated ( Fig.12). An early inhibition in the proliferation of cells treated with CNC*-Au conjugates and X-rays was observed compared to irradiation alone, most likely due to increased radiation-related damage; moreover, in the long term, the cells had lost the ability to generate colonies. The DEFs of CNC*-Au-Glc and CNC*-Au-Man measured at uptake levels achieved with CNC*-Au-Tm were 1.83 and 1.72, respectively ( Fig.12 , Table 1- Fig.17 ).
[0120] In addition, the inventors tested the uptake and biological effects of CNC*-Au conjugates on MCF10a cells, an immortalized breast cell line that is more similar to healthy cells. Although MCF10a cells are known to have induced proliferative behavior (30-hour doubling time) and general plasma membrane translocation of glucose channel 4 (GLUT4) due to growth medium conditions (DMEM+10% NA fetal bovine serum+epidermal growth factor+insulin+hydrocortisone), this model is widely used to provide in vitro estimates of possible side effects of drugs and compounds on normal cells.
[0121] Compared to MDA-MB231 cells, the MCF10a model showed lower uptake levels (i.e., CNC*-Au-Man: 101×10 5 NP / cell; CNC*-Au-Glc: 159×10 5 NP / cell, Fig.11 ) and lower DEF (i.e., CNC*-Au-Man: 1.04; CNC*-Au-Glc: 1.24, calculated using a concentration of 20 μg / mL CNC*-Au conjugate, Fig.12 and Table 1- Fig.17 ) both, thus highlighting the strong selectivity of cancer over normal cells.
[0122] The study has been extended to skin cancer and in particular the A375 human melanoma cell line has been selected. The inventors observed significantly stronger synergy between the CNC*-Au conjugate and X-rays ( Fig.15 and Table 2- Fig.18 , i.e., CNC*-Au-Man: DEF1.81; CNC*-Au-Glc: DEF 2.0). It is noteworthy that, comparing the results of A375 melanoma cell line with the prior art, the inventors observed that the CNC*-Au-Glc calculated using a CNC*-Au-Glc concentration of 20 μg / mL was as high as DEF ( Fig.15 , Table 2- Fig.18). Compared to DEF 1.2 described in the literature using non-targeted AuNPs coated with PEG spacers, and with respect to other AuNPs in the art, this result highlights the greater ability of CNC*-AuN-Glc to effectively enhance the effects of X-rays in radiosensitive cells.
[0123] According to the present invention, and as described above, CNC-Au-Tm composite materials are biocompatible and effective nanocarriers for delivering gold radiosensitizers to desired cells or tissues (preferably cancer cells) because they can act as Trojan horses, allowing internalization and accumulation of AuNPs in desired cells or tissues (preferably tumor cells), and according to a preferred embodiment, delivered to MDA-MB-231 breast cancer cells. Then, the cellulose nanocrystal (CNC) carrier ensures stable AuNP dispersion, overcomes the aggregation of AuNPs in the cell medium and avoids the rapid cell turnover of small AuNPs. Unexpectedly, in addition to the innovation provided by the biocompatible nanomaterials of the present invention, the inventors note that it has been clearly shown that targeting cancer glycan binding proteins is a smart and effective method, confirming their hypothesis. In particular:
[0124] 1. A robust and standardized protocol for the preparation of stable CNC*-Au-Tm composites ( Figure 6 ). The significant improvement of the dispersibility and stability of CNC*-Au-Tm in different media (e.g. HEPES; DMEM; culture cell media) was addressed by increasing the degree of sulfation of the starting cellulose nanocrystals (CNC**) as disclosed above. The functionalization of the target molecule (Tm) (e.g. mannose residues in CNC*-Au-Man) was assessed by turbidimetric assay using specific plant glycan binding lectins, ensuring that the assembly of the target molecule (Tm) on the surface of the nanosystem allowed for proper recognition by glycan binding proteins (e.g. Concanavalin A) ( Fig.13 ).
[0125] 2. CNC*-Au-Tm composites showed no toxicity at relevant high concentrations ( Fig.14 ).
[0126] 3. The CNC*-Au-Tm composite effectively acts as a Trojan horse, significantly ensuring the uptake of the radiosensitizer by the desired cells or tissues (e.g., MDA-MB-231 breast cancer cells) Fig.11). The results confirm that the cellulose carrier can act as a Trojan horse and can deliver a large amount of AuNPs to the desired cells (e.g., tumor cells). In addition, the sugar head group plays a crucial role in the interaction with the desired cells (e.g., tumor cells), significantly affecting the uptake of nanoparticles (NPs). In fact, both glucose and mannose residues allow a large amount of internalization to be obtained, although the nanocomposite dose used is 1 / 5 of the IC50.
[0127] 4. Targeting cancer glycan binding proteins by using a sugar head group as a targeting molecule (Tm) is highly advantageous not only because it increases specific localization on the desired cancer cells, but also improves uptake and retention of the material compared to non-functionalized AuNPs. In addition, the inventors observed slight differences in uptake efficiency between CNC-Au complexed with preferred head groups (preferably mannose or glucose); this may provide further specificity in targeting cancer cells, allowing the selection of the sugar head group most suitable for the tumor type based on specific glycan binding protein expression ( Fig.11 ).
[0128] 5. Internalized CNC-Au-Tm enhanced the efficacy of radiotherapy in both clonogenicity (14 days after irradiation) and short-term counts (24 hours after irradiation) of MDA-MB-231 cells, showing a decrease in proliferation that was highly correlated with the amount of Au measured within the cells, regardless of which sugar head group was present on the CNC-Au ( Fig.11 and Table 1- Fig.17 ). The sugar moieties in the materials of the invention participate in targeting and have been found to have no effect by themselves after internalization, as the amount of gold (Au) alone drives radiosensitization.
[0129] Due to the characteristics of the hybrid cellulose nanocrystal-gold nanoparticles of the present invention, it is possible to obtain a maximized encapsulation of at least one drug inside the material; in particular, the porosity characteristics of cellulose allow for improved encapsulation of the at least one drug, thereby locally driving the action and release of the at least one drug at a site-specific target. The drug is embedded in the cellulose nanocrystal matrix and the bioactive head group determines the bioactivity with an increased level of versatility and reproducibility. Different bioactive head groups determine the focus on different biological effects, so the focus can be adjusted to suit the desired treatment or the desired effect to be achieved. The improved flexibility and reproducibility provided by the hybrid cellulose nanocrystal-gold nanoparticles of the present invention produce significant advantages, preferably in the medical field, and more preferably in tumor treatment. The presence of these bioactive head groups represents a significant advance over known materials and represents an improvement in flexibility and versatility to meet the needs of this technical field, which represents progress.
[0130] Another advantage of the hybrid cellulose nanocrystal-gold nanoparticles of the present invention is the selectivity provided by the functionalization of the material; as mentioned above, the regulation of the biological effect is focused on the possibility of driving the biological effect on the target cell, avoiding healthy cells or healthy tissues to only seek pathological targets. Such selectivity is related to the selection of the targeting molecule and the desired treatment. Since the influence of the hybrid cellulose nanocrystal-gold nanoparticles of the present invention on healthy cells or healthy tissues has been significantly reduced or eliminated, treatment is only performed when necessary, especially tumor cells rather than healthy cells. According to a preferred embodiment, tumor cells show a significant response to the treatment according to the present invention, while healthy cells do not respond.
[0131] Another advantage is the possibility of stoichiometric control of the reaction in the manufacturing process. Thus, the speed of the reaction is not controlled, but by the stoichiometry of the reagents of the invention (see the examples of CNC*-Au-Lac and Figure 6 ), it may be advantageous not to saturate all of the alkyne residues, but to react only a portion of them with the first biologically active head group and subsequently react the remainder with the second head group.
[0132] From the above, it should be demonstrated that the hybrid cellulose nanocrystals-gold nanoparticles of the present invention are new and improved solutions for nanotechnology in medicine: controlled and more efficient delivery and release of therapeutic molecules associated with longer half-life of drugs in vivo and reduced therapeutic toxicity is the gold that the inventors have unexpectedly reached, preferably targeting the treatment of tumors, preferably solid tumors, and even more preferably focusing on radiotherapy with gold particles. Example
[0133] Synthesis of CNC*-Au-Tm.
[0134] CNC*-Au conjugates in which the bioactive head groups are mono- and disaccharide derivatives have been prepared ( Figure 6 ). The monosaccharide and disaccharide derivatives correspond to the tumor targeting moiety (named Tm). Therefore, Tm is selected from glucose (Glc), mannose (Man), lactose (Lac) glycosides, which carry a triethylen PEGylated spacer at the anomeric position of the D-glucose or D-mannose molecules and the D-glucose residue of the lactose molecule, respectively. The PEG spacer contains a terminal azide group (azido-PEG-Tm). The terminal azide group reacts with the terminal alkyne group of LA mounted on the Au surface of CNC*-Au-LA in water via a Cu-catalyzed azide-alkyne reaction ( Figure 6 Depending on the equivalent weight of the reactive azide derivative, the loading of the bioactive head group can be controlled. The CNC*-Au conjugate is easily purified by dialyzing the solution against milliQ water.
[0135] a) Evaluation of the batch-to-batch reproducibility of the functionalization step. In particular, in order to evaluate the high batch-to-batch reproducibility of the functionalization step, azido-PEG-Man was selected as a model Tm. Two equivalents (relative to LA on the CNC*-Au-LA surface) of azido-PEG-Man ( Figure 6 ) were repeated in triplicate. Thus, three CNC*-Au-Man conjugates with an azido-PEG-Man loading of 0.0154±0.001 mmol / 100 mg (based on N content according to elemental analysis) were obtained. The conjugates were used for cellular uptake assays ( Fig.11 ) and colony formation assay ( Fig.12 ).
[0136] The same protocol was used to prepare CNC*-Au-Glc ( Figure 6 ). Using 2.0 equivalents (relative to LA on the surface of CNC*-Au-LA) of azido-PEG-Glc, CNC*-Au-Glc with an azido-PEG-Glc loading of 0.0162 mmol / 100 mg mg (based on N content according to elemental analysis) was obtained. The conjugate was used for cellular uptake assay ( Fig.11 ) and colony formation assay ( Fig.12 ).
[0137] b) Evaluation of loading control of bioactive head groups.
[0138] CNC*-Au conjugates with controlled sugar headgroup loading have been prepared. In particular, azido-PEG-Lac was chosen as a model bioactive headgroup ( Figure 6 ). Three conjugates with lactose residues were prepared with azido-PEG-Lac loading of 0.0126 mmol / 100 mg, 0.0104 mmol / 100 mg, or 0.00738 mmol / 100 mg, respectively, using 1.5, 0.5, or 0.15 equivalents (relative to LA on the surface of CNC*-Au-LA) of azido-PEG-Lac.
[0139] The same protocol was used to prepare CNC*-Au-Glc with a loading of 0.0088 mmol / 100 mg (based on N content according to elemental analysis) of Azide-PEG-Glc using 0.3 equivalents (relative to LA on the surface of CNC*-Au-LA). This conjugate was used to demonstrate the possibility of grafting up to two (2) different head groups by click chemistry (see below).
[0140] Synthesis of CNC*-Au-BODIPY.
[0141] CNC*-Au conjugates have been prepared in which the bioactive head group is a fluorescent probe. Tetramethyl-BODIPY ( Figure 6 ) was used as a model fluorescent probe, and 0.1 equivalent of BODIPY (relative to LA on the surface of CNC*-Au-LA) was used to react with CNC*-Au-LA. max Functionalization was assessed by measuring fluorescence emission at 530 nm.
[0142] Synthesis of CNC*-Au-Glc-BODIPY.
[0143] CNC*-Au conjugates have been prepared in which up to two (2) different head groups are included on the surface of the nanomaterial by click chemistry. In particular, glucose and BODIPY have been selected as model head groups. CNC*-Au-Glc-BODIPY( Figure 6 ) by stepwise iteration of the CuACC reaction ( Figure 5 ). The head group loading was controlled by adjusting the equivalents of the azide-bearing reagent. First, CNC*-Au-LA was reacted with 0.3 equivalents of azido-PEG-Glc (relative to LA on the surface of CNC*-Au-LA) as described above ( Figure 6 Then, the CNC-Au-Glc conjugate was reacted with 0.5 equivalents (relative to LA on the surface of CNC*-Au-LA) of BODIPY with azide ( Figure 6 ), and CNC*-Au-Glc-BODIPY was obtained. The amount of BODIPY was quantitatively estimated by UV-Vis spectroscopy using the molar extinction coefficient of BODIPY in DMSO. CNC*-Au-LA-taurine and CNC*-Au- Synthesis of LA-taurine-BODIPY.
[0144] As mentioned above, the controlled sulfation of the CNC according to the invention does not affect the possibility of treating the OH groups of the glucose of the cellulose to further functionalize the nanoplatform. In fact, the sulfation of the invention does not react all the primary OH groups of the cellulose, but some OH groups remain open for further functionalization. The inventors have advantageously found this, which is different from what is known in the art, for example in CN111803629A, where this is not possible. In this regard, the choice of 2-aminoethanesulfonic acid (taurine, Figure 6) as a model head group and reacted it with CNC*-Au-LA. In particular, the OH group of the Glc residue of CNC*-Au-LA was reacted with 1,1'-carbonyldiimidazole (CDI) to introduce a carboxyl moiety for further extension with taurine. The reaction proceeds through the formation of a reactive imidazole carbamate intermediate, which in turn reacts with taurine to produce a stable carbamate linkage (CNC*-Au-LA-taurine). Then, the possibility of still including a biologically active head group on the gold surface was evaluated. Indeed, the resulting CNC*-Au-LA-taurine was further functionalized and BODIPY has been chosen as a model head group. The CNC*-Au-LA-taurine conjugate was then reacted with 0.5 equivalents (relative to LA on the CNC*-Au-LA surface) of BODIPY ( Figure 6 ) to obtain CNC*-Au-LA-taurine-BODIPY. The amount of BODIPY was quantitatively estimated by UV-Vis spectroscopy using the molar extinction coefficient of BODIPY in DMSO.
[0145] Experimental Section
[0146] Synthesis of CNC*-Au conjugates ( Figures 5 to 6 ).
[0147] Synthesis of CNC* Figure 2 ).
[0148] CNC** (1.0 g, 5.5 mmol glucose units) was added to DMSO (21 mL) stirred vigorously at 25 ° C, the dispersion was stirred for 30 minutes, then SO3-pyridine complex (400 mg, 2.51 mmol) was added, and the dispersion was diluted with DMSO (10.5 mL) to avoid gelation. Two additional batches of sulfur trioxide pyridine complex (400 mg, 2.51 mmol and 500 mg, 3.14 mmol, respectively) were added after 1 hour and 2 hours, respectively. The reaction mixture was stirred for another 2 hours (total reaction time 4 hours), then diluted with acetone (100 mL), and CNC* was precipitated by centrifugation (8000 rpm, 10 minutes). The supernatant was removed, and the solid was dispersed in acetone (100 mL) and precipitated by centrifugation (8000 rpm, 10 minutes). The solid was recovered and dispersed in a NaOH solution (40 mL, 0.1 M in H2O) and stirred for 30 minutes. The dispersion was diluted with milliQ water (60 mL) and dialyzed against milliQ water for 72 hours. The dispersion was then freeze-dried to obtain CNC* as a fluffy white solid. Elemental analysis C 38.44%, H 6.18%, N 0.01% and S 1.99%. The experiment was repeated in triplicate to obtain the degree of sulfation (DS = 0.114 ± 0.007).
[0149] Synthesis of CNC*-Au-LA ( Figure 2 ).
[0150] A stirred solution of 80 mg (0.23 mmol) of tetrachloroauric acid trihydrate in milliQ water (23 mL) was diluted with methanol (207 mL), then 230 mg of CNC* was added, and the mixture was stirred vigorously for 30 minutes. Then, a solution of LA (172 mg, 0.71 mmol) in methanol (1.5 mL) and sodium borohydride (196 mg, 37.8 mmol) were added in sequence, and the mixture was stirred at room temperature for 2 hours. Finally, the CNC*-Au-LA dispersion was dialyzed against milliQ water for 24 hours and freeze-dried to obtain 385 mg of CNC*-Au-LA. ICP-AES: Au 9.9% w / w. Elemental analysis C 30.64%, H 5.47%, N 0.73% and S 3.21%. The experiment was repeated in triplicate, resulting in a LA loading of 0.046±0.003 mmol / 100 mg (based on N content according to elemental analysis). Synthesis of CNC*-Au-Man( Figures 5 to 6 ).
[0151] To a stirred solution of CNC*-Au-LA (60 mg, 0.038 mmol LA) in milliQ water (6.0 mL) was added azido-PEG-Man (26 mg, 0.076 mmol), and the mixture was stirred for 30 minutes. Then, 110 μL of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.0055 mmol) was added. The reaction mixture was stirred at room temperature for 5 hours. Then, another batch of catalyst (110 uL of 50 mM stock solution, 0.0055 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 58 mg CNC*-Au-Man. ICP-AES: Au 9.9 ± % w / w. Elemental analysis C 36.68±0.06%, H 6.12±0.11%, N 1.25±0.04% and S 3.21±0.07%.The experiment was repeated in triplicate to give a loading of 0.0154±0.001 mmol / 100 mg (based on N content according to elemental analysis) of Azide-PEG-Man.
[0152] Synthesis of CNC*-Au-Glc (2.0 equivalents of azido-PEG-Glc, Figures 5 to 6 ).
[0153] To a stirred solution of CNC*-Au-LA (60 mg, 0.038 mmol LA) in milliQ water (6.0 mL) was added azido-PEG-Glc (26 mg, 0.076 mmol), and the mixture was stirred for 30 minutes. Then, 110 uL 50 mM of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.0055 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (110 uL of 50 mM stock solution, 0.0055 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 56 mg CNC*-Au-Glc. ICP-AES: Au 10.6% w / w. Elemental analysis C 36.45%, H 5.59%, N 1.28% and S 4.74%. 0.0162 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Glc was loaded.
[0154] Synthesis of CNC*-Au-Glc (0.3 equivalents of azido-PEG-Glc, Figures 5 to 6 ).
[0155] To a stirred solution of CNC*-Au-LA (100 mg, 0.047 mmol LA) in milliQ water (10 mL) was added azido-PEG-Glc (4.8 mg, 0.014 mmol), and the mixture was stirred for 30 minutes. Then, 141 uL 50 mM of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.0141 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (141 uL of 50 mM stock solution, 0.0141 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 85 mg CNC*-Au-Glc. ICP-AES: Au 9.5% w / w. Elemental analysis C 35.27%, H 5.48%, N 1.04% and S 4.32%. 0.0088 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Glc was loaded.
[0156] Synthesis of CNC*-Au-Lac (1.5 equivalents of azido-PEG-Lac, Figures 5 to 6 ).
[0157] To a stirred solution of CNC*-Au-LA (50 mg, 0.025 mmol LA) in milliQ water (5.0 mL) was added azido-PEG-Lac (18.71 mg, 0.0375 mmol), and the mixture was stirred for 30 minutes. Then, 75 μL of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.00375 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (75 uL of 50 mM stock solution, 0.0375 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 45 mg CNC*-Au-Lac. ICP-AES: Au 10% w / w. Elemental analysis C 36.53%, H 5.62%, N 1.26% and S 5.23%. 0.0126 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Lac was loaded.
[0158] Synthesis of CNC*-Au-Lac (0.5 equivalents of azido-PEG-Lac, Figures 5 to 6 ).
[0159] To a stirred solution of CNC*-Au-LA (50 mg, 0.025 mmol LA) in milliQ water (5.0 mL) was added azido-PEG-Lac (6.23 mg, 0.0125 mmol), and the mixture was stirred for 30 minutes. Then, 75 uL 50 mM of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.00375 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (75 uL of 50 mM stock solution, 0.00375 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 45 mg CNC*-Au-Lac. ICP-AES: Au 10.6% w / w. Elemental analysis C 36.35%, H 5.42%, N 1.17% and S 5.14%. 0.0104 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Lac was loaded.
[0160] Synthesis of CNC*-Au-Lac (0.15 equivalents of azido-PEG-Lac, Figures 5 to 6 ).
[0161] To a stirred solution of CNC*-Au-LA (50 mg, 0.025 mmol LA) in milliQ water (5.0 mL) was added azido-PEG-Lac (6.23 mg, 0.0025 mmol), and the mixture was stirred for 30 minutes. Then, 75 uL 50 mM of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.00375 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (75 uL of 50 mM stock solution, 0.00375 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the reaction mixture was dialyzed with milliQ water for 24 hours and freeze-dried to obtain 45 mg CNC*-Au-Lac. ICP-AES: Au 10.7% w / w. Elemental analysis C 36.17%, H 5.50%, N 1.04% and S 4.98%. 0.00738 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Lac was loaded.
[0162] Synthesis of CNC*-Au-BODIPY( Figures 5 to 6 ).
[0163] To CNC * -Au-LA (30mg, 0.014mmol LA) in dimethylformamide (3.0mL) through stirring solution azido-tetramethyl-BODIPY (510μg, 1.4μmol), and the mixture was stirred for 30 minutes. Then, 42uL50mM ratio of 1: 1 CuSO4: sodium ascorbate mixture solution (0.0021mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (42uL of 50mM stock solution, 0.0021mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was diluted with dichloromethane and centrifuged (9000rpm, 10 minutes). The solid was recovered, dispersed in 10mL methanol and precipitated by centrifugation (9000rpm, 10 minutes). The solid was collected, dispersed in a mixture of 9:1 water:methanol at 1.0 mg / mL, and dialyzed against a mixture of 9:1 water:methanol for 48 hours (changing the solution twice) and against water for 24 hours. The dispersion was then freeze-dried to give CNC*-Au-BODIPY (25 mg) at λ max = Provides fluorescence emission at 530 nm. Synthesis of CNC*-Au-LA-taurine ( Figures 5 to 6 ).
[0164] To a stirred dispersion of CNC*-Au-LA (45 mg) in anhydrous dimethyl sulfoxide (2.5 mL) was added carbonyl diimidazole (81 mg, 0.5 mmol) under a nitrogen atmosphere. The mixture was stirred at room temperature for 3 hours, then taurine (250 mg, 2 mmol) was added and the mixture was stirred at room temperature under a nitrogen atmosphere for 11.5 hours. Anhydrous sodium carbonate (53 mg, 0.5 mmol) was then added and the mixture was stirred for an additional 30 minutes. The dispersion was diluted with milliQ water (47.5 mL) and dialyzed with water for 24 hours (changing the water three times) and freeze-dried to give 38 mg of CNC*-Au-LA-taurine. ICP-AES Au 9.2% w / w. Elemental analysis C 34.55%, H 5.482%, N 1.2%, 4.518%. Taurine loading 0.033 mmol / 100 mg (based on N content according to elemental analysis). Synthesis of CNC*-Au-LA-taurine-BODIPY ( Figures 5 to 6 ).
[0165] To CNC * -Au-La-taurine (20mg, 0.010mmol LA) in dimethylformamide (2.0mL) through stirring solution azido-tetramethyl-BODIPY (1.9mg, 5μmol), and the mixture was stirred for 30 minutes. Then, 30uL50mM ratio was added to be 1: 1 CuSO4: sodium ascorbate mixture solution (0.0015mmol). The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (30uL of 50mM stock solution, 0.0015mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was diluted with dichloromethane and centrifuged (9000rpm, 10 minutes). Solid was recovered, dispersed in 25mL methanol and precipitated four times by centrifugation (9000rpm, 10 minutes). The solid was collected, dispersed in a mixture of 9:1 water:methanol at 1.0 mg / mL, and dialyzed against a mixture of 9:1 water:methanol for 48 hours (changing the solution twice) and against water for 24 hours. The dispersion was then freeze-dried to give CNC*-Au-taurine-BODIPY (20 mg) at λ max =530 nm provided fluorescence emission. The amount of BODIPY was quantitatively estimated by UV-Vis spectroscopy using the molar extinction coefficient of BODIPY in DMSO. The result was 0.47% w / w BODIPY.
[0166] Synthesis of CNC*-Au-Glc-BODIPY ( Figures 5 to 6 ).
[0167] To CNC * -Au-Glc (25mg, 0.012mmol LA) in dimethylformamide (2.5mL) through stirring solution azido-tetramethyl-BODIPY (3.5mg, 9.5μmol), and the mixture was stirred for 30 minutes. Then, 57uL50mM ratio was added to be 1: 1 CuSO4: sodium ascorbate mixture solution (0.0029mmol). The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (57uL of 50mM stock solution, 0.0029mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was diluted with dichloromethane and centrifuged (9000rpm, 10 minutes). Solid was recovered, dispersed in 10mL methanol and precipitated by centrifugation (9000rpm, 10 minutes). The solid was collected, dispersed in a mixture of 9:1 water:methanol at 1.0 mg / mL, and dialyzed against a mixture of 9:1 water:methanol for 48 hours (changing the solution twice) and against water for 24 hours. The dispersion was then freeze-dried to give CNC*-Au-BODIPY (25 mg) at λ max =530 nm provided fluorescence emission. The amount of BODIPY was quantitatively estimated by UV-Vis spectroscopy using the molar extinction coefficient of BODIPY in DMSO. The result was 1.56% w / w BODIPY.
[0168] Synthesis of CNC**-Au conjugates ( Figure 8 ).
[0169] Synthesis of CNC**-Au-LA ( Figure 8 ).
[0170] A stirred solution of 80 mg (0.23 mmol) of tetrachloroauric acid trihydrate in milliQ water (23 mL) was diluted with methanol (207 mL), then 230 mg of CNC** was added, and the mixture was stirred vigorously for 30 minutes. Then, a solution of LA (172 mg, 0.71 mmol) in methanol (1.5 mL) and sodium borohydride (196 mg, 37.8 mmol) were added in sequence, and the mixture was stirred at room temperature for 2 hours. Finally, the CNC**-Au-LA solution was dialyzed against water milliQ (a precipitate formed in the dialysis bag) for 24 hours and freeze-dried to obtain 392 mg of CNC**-Au-LA. ICP-AES: Au 9.18% w / w. The reaction was repeated twice to obtain two different batches: Batch A: Elemental analysis C 31.38%, H 5.26%, N 1.02% and S 4.86%. LA loading was 0.0720 mmol / 100 mg (based on N content according to elemental analysis) and Batch B: Elemental analysis C 2 7.76%, H 5.10%, N 0.95% and S 4.08%. LA loading was 0.067 mmol / 100 mg (based on N content according to elemental analysis).
[0171] Synthesis of CNC**-Au-Man( Figure 8 ).
[0172] To a stirred solution of CNC**-Au-LA (30 mg, 0.021 mmol LA) in milliQ water (3.0 mL) was added Azide-PEG-Man (14 mg, 0.042 mmol), and the mixture was stirred for 30 minutes. Then, 63 uL of a 50 mM solution of a 1:1 mixture of CuSO4: sodium ascorbate (0.0031 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (63 uL of a 50 mM stock solution, 0.0031 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was dialyzed against milliQ water for 24 hours (a precipitate formed in the dialysis bag) and freeze-dried to give 29 mg CNC**-Au-Man. ICP-AES: Au 9.5% w / w. Elemental analysis C 36.06%, H 5.39%, N 1.60% and S4.96%. The loading was 0.0155 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Man.
[0173] Synthesis of CNC**-Au-Fuc( Figure 8 ).
[0174] To a stirred solution of CNC**-Au-LA (67 mg, 0.048 mmol) in milliQ water (6.7 mL) was added Azide-PEG-Fuc (31 mg, 0.096 mmol) and the mixture was stirred for 30 minutes. Then, 144 uL of a 50 mM solution of a 1:1 mixture of CuSO4: sodium ascorbate (0.0072 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (144 uL of a 50 mM stock solution, 0.0072 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was dialyzed against milliQ water for 24 hours (precipitate formed in the dialysis bag) and freeze-dried to give 27 mg CNC**-Au-Fuc. ICP-AES: Au 10.7% w / w. Elemental analysis C 35.02%, H 4.55%, N 1.58% and S 5.7%. The loading was 0.0132 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Fuc.
[0175] Synthesis of CNC**-Au-Glc( Figure 8 ).
[0176] To a stirred solution of CNC**-Au-LA (30 mg, 0.021 mmol) in milliQ water (3.0 mL) was added azido-PEG-Glc (14 mg, 0.042 mmol), and the mixture was stirred for 30 minutes. Then, 12 uL 50 mM of a 1:1 ratio of CuSO4: sodium ascorbate mixture solution (0.060 mmol) was added. The reaction mixture was stirred at room temperature for 2 hours. Then, another batch of catalyst (12 uL of 50 mM stock solution, 0.060 mmol) was added and the mixture was stirred at room temperature for 12 hours. Then, the mixture was dialyzed with milliQ water for 24 hours (precipitate formed in the dialysis bag) and freeze-dried to obtain 27 mg CNC**-Au-Glc. ICP-AES: Au 9.8% w / w. Elemental analysis C 30.47%, H 4.34%, N 2.21% and S4.26%. The loading amount was 0.008 mmol / 100 mg (based on the N content according to elemental analysis) of Azide-PEG-Glc.
[0177] Resuspension of CNC*-Au conjugate.
[0178] One day before the experiment, the powder formulation of CNC*-Au conjugate was first vortexed for 2 minutes, and milliQ distilled water was added dropwise while vortexing to reach a final concentration of 5.0 mg / ml. The 5.0 mg / ml stock vials were then sonicated for 30 cycles (60 seconds on, 5 seconds off) at 4°C in a Bioruptor sonication bath (Biosense), and after sonication, the vials were placed overnight to stabilize.
[0179] On the day of the experiment, the 5.0 mg / ml stock solution was diluted to 1.0 mg / ml by adding milliQ distilled water and further sonicated for 30 cycles (60 seconds on, 5 seconds off) at 4° C. The 1.0 mg / ml vial was added to the cell growth medium to reach the desired final concentration.
[0180] Cytotoxicity assay ( Fig.14 and Fig.17 )
[0181] MDA-MB-231, MCF10A and A375 cells were plated in 96-well plates at 5k / plate and left to attach overnight. At t0, cells were treated with CNC*-Au conjugates at different concentrations (0, 2.5, 5, 10, 20, 50 and 100 μg / ml) for 24 hours, and the CNC*-Au conjugates were functionalized with glucose or mannose in a final volume of 100 μl. After incubation with CNC*-Au conjugates, viability was assessed by cell titer glo (PROMEGA) according to the manufacturer's protocol, and luminescence values were normalized for untreated controls.
[0182] Short-term determination
[0183] MDA-MB-231, MCF10A and A375 cells were plated in 6 cm plates at 200 k / plate and left to attach overnight. At t0, cells were treated with CNC*-Au-Glc and CNC*-Au-Man (the CNC*-Au-Glc and CNC*-Au-Man were functionalized with glucose or mannose, respectively) at different concentrations (2.5, 5, 10 and 20 μg / ml or remained untreated) for 24 hours in a final volume of 2.0 ml. After incubation of the CNC*-Au-Tm conjugate, cells were irradiated with X-rays at 100 kV and 10 mA using a Faxitron CP-160 (Faxitron X-ray Company) to obtain a final irradiation of 0, 0.5, 1, 2, 4 and 8 grays in the radiation control alone and 0, 0.5, 1, 2 and 4 grays in the CNC*-Au-Tm treatment point. 24 hours after irradiation, cells have been collected in trypsin and PI exclusion assay has been performed using MACSQuant X flow cytometer (Miltenyi Biotech) to count and assess viability. Debris was excluded by size (forward scatter) and granularity (side scatter) evaluation.
[0184] Final data were collected from 3 independent experiments, each of which was repeated 3 times (n=9). Values were normalized to no CNC*-Au-Tm, no irradiation control cells.
[0185] Colony formation assay ( Fig.12 and Fig.16 )
[0186] MDA-MB-231, MCF10A and A375 cells were plated in 6 cm plates at 200 k / plate and left to attach overnight. At t0, cells were treated with CNC*-Au-Glc and CNC*-Au-Man (the CNC*-Au-Glc and CNC*-Au-Man were functionalized with glucose or mannose, respectively) at different concentrations (2.5, 5, 10, 20 and 50 μg / ml or remained untreated) for 24 hours in a final volume of 2.0 ml. After CNC*-Au-Tm incubation, cells were irradiated with X-rays at 100 kV and 10 mA with Faxitron CP-160 (Faxitron X-ray Company) to obtain final irradiation of 0, 1, 2 and 4 grays. A few minutes after irradiation, cells were counted and re-plated in 6-well plates (100 and 200 cells-well) at 2 densities and left to grow for up to 14 days. Afterwards, colonies were stained with crystal violet and counted under a microscope, considering valid colonies with more than 50 cells. The survival fraction was calculated as the ratio between the colonies counted and the cells plated.
[0187] Method for DEF / SER calculation (Table 1- Fig.17 and Table 2- Fig.18 )
[0188] DEF was calculated from the clonogenic assay using PRISM software to first estimate a nonlinear regression-linear quadratic model with the equation Y=100*exp(-1*(A*X+B*^2)) for each type of CNC*-AuNP at each concentration in each cell line. DEF was then measured as the ratio between the X-ray dose required to give the same 60% survival fraction in the various conditions of CNC*-AuNPs and in control cells irradiated only.
[0189] Formula DEF = (X-ray dose at 60% survival fraction in irradiation plus NP) / (X-ray dose at 60% survival fraction in irradiation only)
[0190] The SER was calculated from the clonogenic assay using PRISM software and was defined as the ratio between the area under the curve for irradiation plus CNC*-Au at a specific concentration and irradiation alone (Y = surviving fraction X = X-ray boost dose).
[0191] Formula SER = (area under the curve of irradiated cells plus NP) / (area under the curve of irradiated cells only)
[0192] Cellular uptake assessment ( Fig.11 and Fig.15 ).
[0193] MDA-MB-231, MCF10A and A375 cells were plated in 24-well plates at 40k / well and placed to attach overnight. At t0, cells were treated with CNC*-Au-LA and CNC*-Au-Glc and CNC*-Au-Man (the CNC*-Au-Glc and CNC*-Au-Man were functionalized with glucose or mannose, respectively) at different concentrations (2.5, 5, 10, 20 and 50 μg / ml or kept untreated) for 24 hours, and the final volume was 300 μl. After CNC*-Au incubation, cells were washed 3 times with 100 μl PBS, then detached and collected in 100 μl trypsin EDTA solution. MilliQ distilled water was added to the detached cells in trypsin and violently pipetted to cause cell lysis due to isotonic buffer. Lysate can be stored at 20°C. 400 μl of aqua regia was added to the lysate and placed under a chemical fume hood for 72 hours. After incubation, 1500 μl of MilliQ distilled water was added and mixed by gently shaking the vial.
[0194] Turbidimetric determination ( Fig.13 ).
[0195] Turbidimetric measurements were performed in triplicate using a 96-well plate and biorad plate reader. ConA was dissolved in 10mM HEPES (pH 7.4) at a concentration of 20 μM, and 1mM MnCl2 and CNC*-Au-Man were dispersed in milliQ water at a concentration of 0.1%. The two solutions were then mixed in a 96-well plate and diluted with 10mM HEPES (pH 7.4), 1mM MnCl2 to obtain 200 μL of 10 μM ConA and 0.01% CNC*-Au-Man. The absorbance at 490 nm was read every minute for 30 minutes.
[0196] In the second article to determine the amount of ConA required to observe nanoparticle agglutination, 0.01% w / v CNC*-Au-Man was titrated with ConA concentrations ranging from 5 to 10000 nM and the absorbance at 490 nm was measured after 10 minutes.
[0197] For flow cytometric analysis of treated glioblastoma cells ( Fig.19 A)
[0198] U251 cells were plated in 6-well plates at 100 k / plate and left to attach overnight. At t0, cells were treated with 20 μg / ml of CNC*-Au-Glc (functionalized with glucose) or kept untreated for 24 hours in a final volume of 2.0 ml. After the CNC*-Au-Tm incubation, cells were irradiated with X-rays at 100 kV and 10 mA using a Faxitron CP-160 (Faxitron X-ray Company) to obtain final irradiations of 0, 1, 2, and 4 grays. A few minutes after irradiation, cells were counted and re-plated in 6-well plates at a density of 200 cells / well and left to grow for up to 14 days. At 24 h after treatment, early cell death in response to treatment was measured using a propidium iodide dye exclusion assay, which revealed that in the presence of CNC-AuNPs, the cytotoxic properties of x-ray radiotherapy were significantly enhanced compared to the control group treated with radiotherapy alone without pre-incubation with CNC-AuNPs ( Fig.19 A). CNC-AuNPs alone did not induce acute toxicity, thus confirming the good biocompatibility of the proposed nanosystem and its ability to act as a radiosensitizer.
[0199] For the colony formation assay of glioblastoma cells ( Fig.19 B)
[0200] U251 cells were plated in 6-well plates at 100k / plate and placed to attach overnight. At t0, cells were treated with 10 μg / ml of CNC * -Au-Glc (functionalized with glucose) or kept untreated for 24 hours, with a final volume of 2.0 ml. After CNC * -Au-Tm incubation, cells were irradiated with X-rays at 100kV and 10mA by Faxitron CP-160 (Faxitron X-ray Company) to obtain the final irradiation of 0, 1, 2 and 4 grays. A few minutes after irradiation, cells were counted and plated again in 6-well plates at a density of 200 cells / well, and growth was placed for up to 14 days. Afterwards, colonies were stained with crystal violet and counted, considering the effective colonies with more than 50 cells. The survival score was calculated as the ratio between the colonies counted and the cells plated. Fig.19 The results in B show that CNC-AuNPs improve the ability of radiotherapy to limit tumor cell proliferation.
Claims
1. A multifunctional hybrid CNC-Au based nanoplatform containing at least one and at most two orthogonal anchoring points, preferably represented by the OH groups of the glucose residues of CNCs and the alkynes on the Au surface.
2. The multifunctional hybrid CNC-Au based nanoplatform according to claim 1, wherein at least one bioactive head group is conjugated to at least one orthogonal anchoring point.
3. The multifunctional hybrid CNC-Au based nanoplatform according to any of the preceding claims, wherein the bioactive head group is a carbohydrate, preferably a sugar, and even more preferably selected from glucose and mannose, lactose, fucose, rhamnose and Lewis type antigens.
4. The multifunctional hybrid CNC-Au based nanoplatform according to any one of the preceding claims, wherein gold nanoparticles (AuNPs) are embedded on the cellulose nanocrystal matrix and have a size of ≤5 nm, preferably about 5.0±1.0 nm.
5. A conjugate comprising the multifunctional hybrid CNC-Au based nanoplatform according to any one of the preceding claims, preferably a monofunctional or bifunctional conjugate.
6. The multifunctional hybrid CNC-Au based nanoplatform or a conjugate containing the multifunctional hybrid CNC-Au based nanoplatform according to any one of the preceding claims, for use in treating tumors, preferably solid tumors.
7. The multifunctional hybrid CNC-Au-based nanoplatform or a conjugate containing the multifunctional hybrid CNC-Au-based nanoplatform according to any one of the preceding claims for use according to claim 6, wherein the tumor is selected from breast cancer, uterine cancer, brain and central nervous system cancer, lung cancer, liver cancer, kidney cancer, testicular cancer, pancreatic cancer, skin cancer, thyroid cancer, intestinal cancer, head and neck cancer, ovarian cancer, gastric cancer, colon cancer, bladder cancer, prostate cancer and urinary tract cancer, eye cancer, oral cancer and oropharyngeal cancer, HIV / AIDS-related cancers, hematopoietic system cancers and lymphomas, and sarcomas of various tissues, preferably triple-negative breast cancer, glioblastoma and melanoma.
8. The multifunctional hybrid CNC-Au based nanoplatform or a conjugate containing the multifunctional hybrid CNC-Au based nanoplatform according to any one of the preceding claims, for use in radiotherapy, immunotherapy, photodynamic therapy, boron neutron capture therapy (BNCT) and cancer therapy diagnosis.
9. A method for obtaining a multifunctional hybrid CNC-Au based nanoplatform, the method comprising the following steps: a) Preparation of CNC*: treating raw cellulose nanocrystals with a sulfating agent and a solvent to obtain cellulose nanocrystals with controlled sulfation; and b) Preparation of CNC*-Au-LA: The CNC* with controlled sulfation as obtained in step a) was treated with HAuCl4 / NaBH4, lipoamide (LA) in a methanol / water solution to obtain a hybrid nanoplatform of CNC*-Au-LA.
10. The method according to claim 2, wherein step (b) is a one-pot reaction.
11. The method of claim 4, wherein the sulfating agent is a mixture of SO3 / pyridine and the solvent is dimethyl sulfoxide (DMSO).
12. The method according to any one of the preceding claims, further comprising a step wherein the CNC*-Au-LA is purified by dialysis.
Citation Information
Patent Citations
Organic-inorganic hybrid multifunctional biological material based on nanocellulose crystals and preparation method and application thereof
CN111803629A